In‐situ high‐temperature Raman spectroscopic studies of the vibrational characteristics and microstructure evolution of sodium tungstate dihydrate crystal during heating and melting. (10th July 2018) - Wang, Jian; You, Jinglin; Wang, Min; Lu, Liming; Sobol, Alexander A.; Wan, Songming
Abstract: In‐situ studies of the vibrational characteristics and microstructure evolution of the Na2 WO4 ·2H2 O (sodium tungstate dihydrate) crystal during the temperature‐induced solid‐state phase transformation and melting process were carried out using high‐temperature Raman spectroscopic technique. Results showed that the thermal decomposition process of the Na2 WO4 ·2H2 O crystal takes place mainly within the temperature range of 348–383 K, along with the structure transforming from the orthorhombic to cubic symmetry. As the sample temperature increased further, another solid‐state phase transformation from the cubic to orthorhombic structure was observed approximately at 893 K before melting occurred at 1023 K. Although the isolated [WO4 ] 2− tetrahedron was preserved within the entire temperature range from room temperature to 1023 K, subtle changes were observed with the mean bond length of W–O bonds in the tetrahedron unit. Furthermore, Raman active vibrational modes of Na2 WO4 ·2H2 O, two Na2 WO4 crystal phases, and corresponding melt were assigned based on the density functional theory simulation and compared with the literature data. Finally, four‐molecule cluster arranged as T d symmetry is considered to be the most likely configuration in the molten state according to density functional theory simulation based on the different multimolecular clusters proposed. Abstract : In‐situ Raman spectra of the polycrystalline Na2 WO4 ·2H2 O from room temperature to 1023 K were investigated systematically. The vibrational modes of Na2 WO4 ·2H2 O, two Na2 WO4 crystal phases, and corresponding melt were assigned based on density functional theory simulation. Microstructure evolution of [WO4 ] 2− during dehydration, solid‐state phase transformation, and melting process was evaluated. Several multimolecular cluster models were constructed, and their Raman active vibrational modes were simulated in order to determine the most likely arrangement of [WO4 ] 2− tetrahedra in the molten state.